From participation to systematization: A scoping review of theoretical frameworks guiding process evaluations in community mental health interventions - Rainer Mere; Merike Sisask; Peeter Värnik; Chantal Van Audenhove (PLoS ONE, 2026)
Background Process evaluations are essential for understanding how community mental health interventions are implemented and why they succeed or fail. While numerous theoretical frameworks exist to guide such evaluations, the landscape of framework use in mental health contexts remains uncharted, limiting methodological guidance for researchers and practitioners. Methods Scoping review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines. Systematic searches of three databases (PubMed, Web of Science, EBSCOhost) identified 1,143 records, from which process evaluations of community mental health interventions published between 2006 and 2025 were selected. Data extraction captured framework characteristics, study context, and methodological features. Frameworks were inductively categorized into a hierarchical typology based on theoretical orientation and stated function. Results Eighty-three studies met inclusion criteria, employing 54 distinct primary frameworks organized into 14 categories. Implementation science frameworks dominated (39.8%), followed by process evaluation-specific frameworks (8.4%), behavior change theories (8.4%), and participatory approaches (6.0%). A marked temporal shift was observed: participatory and community-based frameworks characterized early publications (23.8% in 2006–2015) but were absent as primary frameworks after 2015, while implementation science frameworks rose from 14.3% to over 50% of studies. Geographic concentration in North America (54.2%) and high-income countries (83.1%) was pronounced. Conclusions The field has undergone a paradigm shift from community-engaged to systematized evaluation approaches. While framework consolidation offers methodological consistency, the decline of participatory approaches raises questions about the role of community voice in evaluation design. We propose a typology to guide framework selection and identify priorities for methodological development in community mental health process evaluation.